STATE POLICY OF PROMOTING ENTREPRENEURSHIP DEVELOPMENT IN UKRAINE: FROM THE CLASSICAL IMPROVEMENT OF THE BUSINESS CLIMATE TO OVERCOMING THE CHALLENGES OF WAR - MEISH, Alla; SHPYLOVYI, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the study is to identify new challenges of the state policy of entrepreneurship development in war conditions, generalization of existing and development of new tools and means of the state policy of stimulating the development of entrepreneurship in the system of functioning and development of the national economy. The study revealed the relevance of the problem of the decline in business activity of the population in the conditions of a full-scale war, which is natural, as well as the justification of effective and efficient means of the state policy of restoring incentives to conduct business. It was established that the development of entrepreneurship is largely determined by a favorable business climate. In turn, its basic characteristics are the absence or at least a low natural level of transaction costs of doing business, transparency of information and competition, and an adequate level of protection of private property rights. It was concluded that the further improvement of the business environment of Ukraine requires the implementation of a complex of organizational and economic tools aimed at improving the accessibility of small and medium-sized business entities to markets, protection and accessibility of activity rights, attraction of economic resources, development of market and business infrastructure, protection information, involvement of management technologies, implementation of investments and innovations. The most critical problematic aspects (challenges) of domestic business in the conditions of war have been identified, taking into account the specifics of the industry. It was established that the state in its policy of stimulating the development of enterprises in wartime should take into account such aspects as insurance, preservation of the material, technical and technical and technological base of enterprises, assistance in attracting cheap long-term loans for the reconstruction, preservation and modernization of production facilities, improvement of the security system enterprises with working capital, preservation of human and, in particular, labor and intellectual capital of domestic business entities. The scientific novelty and applied value of the research results lies in the improvement of the methodological and applied principles of the formation of a system of tools for improving the entrepreneurial climate both in standard conditions and in a critically complicated environment during a full-scale war.